1991
DOI: 10.1128/jcm.29.5.883-888.1991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gen-Probe DNA probe test and culture for the detection of Neisseria gonorrhoeae in endocervical specimens

Abstract: A 2-h nonisotopic DNA probe assay for the direct detection of Neisseria gonorrhoeae in urogenital specimens has recently been modified (PACE 2; Gen-Probe, San Diego, Calif.). The new assay format was developed to increase the sensitivity of the assay and simplify procedural steps. In this study, the new DNA probe test was compared with a culture reference method for the detection of N. gonorrhoeae in endocervical specimens. The results of the DNA probe test were expressed as a ratio of relative light units (RL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…After resolution of discrepant results, the PACE 2C assay had a sensitivity, a specificity, and positive and negative predictive values of 96.3, 98.8, 92.9, and 99.4%, respectively (Table 3). These values compare favorably with the results obtained from testing when single DNA probes were used (8,12,14,16,17,19). The culture sensitivities for C. trachomatis and N. gonorrhoeae in this study were 89.2 and 88.9%, respectively, suggesting that the use of culture as the reference assay, or gold standard, should be reconsidered.…”
Section: Results After Resolutionsupporting
confidence: 76%
See 1 more Smart Citation
“…After resolution of discrepant results, the PACE 2C assay had a sensitivity, a specificity, and positive and negative predictive values of 96.3, 98.8, 92.9, and 99.4%, respectively (Table 3). These values compare favorably with the results obtained from testing when single DNA probes were used (8,12,14,16,17,19). The culture sensitivities for C. trachomatis and N. gonorrhoeae in this study were 89.2 and 88.9%, respectively, suggesting that the use of culture as the reference assay, or gold standard, should be reconsidered.…”
Section: Results After Resolutionsupporting
confidence: 76%
“…Falsepositive PACE 2 assay results with low RLU values have been observed in other studies (4,8,12,14,19). Some investigators have suggested that a borderline zone for retesting of lowvalue positive or high-value negative results be developed to help in the evaluation of these samples (4,8,9,19,23,24). In using the PACE 2C assay, an intermediate zone for low-value positive results may not be needed, since all positive samples are retested by single probes to identify the organism(s).…”
Section: Results After Resolutionmentioning
confidence: 96%
“…The possibility of being unable to culture N. gonorrhoeae because of harsh transport conditions led us to investigate the Gen-Probe system as an alternative to culture for specimens that are mailed in to the laboratory. Previous studies by Panke et al (8) have indicated the Gen-Probe test for N. gonorrhoeae is comparable to culture when specimens are processed and tested under optimal conditions for both assays. We also found that the Gen-Probe PACE 2 assay system is reliable, but the assay has the advantage of detecting many more additional positive specimens than culture does for specimens that are mailed in to the laboratory.…”
Section: Discussionmentioning
confidence: 98%
“…A system reported to be stable and accurate for detecting both N. gonorrhoeae and Chlamydia trachomatis based on DNA probes complementary to rRNA is the Gen-Probe PACE 2 assay (Gen-Probe Inc., San Diego, Calif.). This assay, which is based on a chemiluminescence detection system, has been shown to perform comparably to culture for N. gonorrhoeae and C. trachomatis detection on the basis of parallel testing of duplicate samples (4,6,8). However, prior studies involved the testing of limited numbers of specimens from local sites and did not involve significant specimen transport time.…”
mentioning
confidence: 99%
“…Numerous DNA/RNA‐based noncultural methods, mainly NAATs, for the identification of N. gonorrhoeae have been developed. The PACE 2 assay (Gen‐Probe) has been used for several years to detect 16S rRNA of N. gonorrhoeae (63) by DNA probe hybridisation. Digene Hybrid Capture 2 (HC2) CT/GC including HC2 GC‐ID for N. gonorrhoeae (Digene Corporation) is a newer RNA‐probe based assay that identifies specific DNA sequences of the chromosome as well as the cryptic plasmid of N. gonorrhoeae (64).…”
Section: Laboratory Diagnosis Of Neisseria Gonorrhoeaementioning
confidence: 99%